Neuromarketing and memory: Implications for Advertising - Serrano Abad, Nuria; de Balanzó Bono, Cristina (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2013)
Memory is a relevant and fundamental part of advertising and advertising research. It is usually obvious to include the study of memory on any given research project. But despite everything we have learned about memory throughout the years, we still haven’t completely understood how it influences advertising effec-tiveness. Our point of view is that this is about to change thanks to relevant findings from cognitive neuro-science, and the development of neuromarketing. This article summarizes current findings on the subject as a starting point for other researchers in the field.